The Oklahoma thrombotic thrombocytopenic purpura-haemolytic uraemic syndrome Registry - George, J. N.; Vesely, S. K.; Terrell, D. R.; Deford, C. C.; Reese, J. A.; Al-Nouri, Z. L.; Stewart, L. M.; Lu, K. H.; Muthurajah, D. S. (Hämostaseologie, 2013)
The Oklahoma Thrombotic Thrombocytopenic Purpura-Haemolytic Uraemic Syndrome (TTPHUS) Registry has a 24 year record of success for collaborative clinical research, education, and patient care. This article tells the story of how the Registry began and it describes the Registry’s structure and function. The Registry provides a model for using a cohort of consecutive patients to investigate a rare disorder. Collaboration between Oklahoma, United States and Bern, Switzerland has been the basis for successful interpretation of Registry data.Registry data have provided new insights into the evaluation and management of TTP. Because recovery from acute episodes of TTP has been assumed to be complete, the increased prevalence of hypertension, diabetes, depression, and death documented by long-term follow-up was unexpected. Registry data have provided opportunities for projects for students and trainees, education of physicians and nurses, and also for patients themselves. During our follow-up, patients have also educated Registry investigators about problems that persist after recovery from an acute episode of TTP. Most important, Registry data have resulted in important improvements for patient care.
Keywords: TTP-HUS; thrombotic thrombocytopenic purpura; cohort studies; rare disorders